Calligraphic Design in Fractal Model Based on Rectangle Collage Decomposition - Darmanto, Tedjo (RSF Conference Series: Business, Management and Social Sciences, 2021)
A fractal model can deliver the beauty of self-similarity feature to be used in designing artistic things such as calligraphic characters. The fractal model can deliver the power of mathematics to be used in modeling the complex things that can be handled by computer programs. This paper delivers the short-cut way to design the artistic calligraphic characters based on the modification of the existing form of the simple rectangle fractal object to construct the stroke form of the calligraphic character as the simple solution of the inverse problem. The upright collage component design of rectangle fractal object can be decomposed into many cells of collage component of a calligraphic character with equal size in the right position of the cells according to the stroke of calligraphic character designed. The short-cut way to encode the fractal object is by copy-editing the representative IFS code based on the position of the cells according to the position of each component of the stroke. The calligraphic characters in fractal form as the collection of IFS code set are the representation of the affine coefficient functions, so they can be easily modified by means of the affine transformation function to any desired form.